Diminished AdipoR1/APPL1 Interaction Mediates Reduced Cardioprotective Actions of Adiponectin against Myocardial Ischemia/Reperfusion Injury in Type-2 Diabetic Mice - Chao Ren; Wei Yi; Bo Jiang; Erhe Gao; Jiali Liang; Bo Zhang; Zhe Yang; Dezhi Zheng; Yong Zhang (Hindawi Limited, 2023)
Background. Obesity-related diseases have important implications for the occurrence, severity, and outcome of ischemic heart disease. Patients with obesity, hyperlipidemia, and diabetes mellitus (metabolic syndrome) are at increased risk of heart attack with decreased plasma lipocalin levels, and lipocalin is negatively correlated with heart attack incidence. APPL1 is a signaling protein with multiple functional structural domains and plays an important role in the APN signaling pathway. There are two known subtypes of lipocalin membrane receptors, AdipoR1 and AdipoR2. AdioR1 is mainly distributed in skeletal muscle while AdipoR2 is mainly distributed in the liver. Objective. To clarify whether the AdipoR1-APPL1 signaling pathway mediates the effect of lipocalin in reducing myocardial ischemia/reperfusion injury and its mechanism will provide us with a new approach to treat myocardial ischemia/reperfusion injury using lipocalin as an intervention and therapeutic target. Methods. (1) Induction of hypoxia/reoxygenation in SD mammary rat cardiomyocytes to simulate myocardial ischemia/reperfusion; (2) downregulation of APPL1 expression in cardiomyocytes to observe the effect of lipocalin on myocardial ischemia/reperfusion and its mechanism of action. Results. (1) Primary mammary rat cardiomyocytes were isolated and cultured and induced to simulate MI/R by hypoxia/reoxygenation; (2) lipocalin inhibited H/R-induced apoptosis in cardiomyocytes; and (3) APN attenuated MI/R injury through AdipoR1-APPL1 and the possible mechanism. Conclusion. This study demonstrates for the first time that lipocalin can attenuate myocardial ischemia/reperfusion injury through the AdipoR1-APPL1 signaling pathway and that the reduction of AdipoR1/APPL1 interaction plays an important role in cardiac APN resistance to MI/R injury in diabetic mice.